DESMOID-TYPE FIBROMATOSIS OF THE BREAST IN A MALE PATIENT - Melo, Márcia Portela; Magdalena, Luiza Guimarães de; Cavalheiro, José Antonio Crespo; Graudenz, Márcia Silveira; Brazan, Murilo de Lima (Mastology, 2020)
Introduction: The desmoid breast tumor was first described in 1832, by Mac Farianec. It originates in the parenchyma or in the thoracic wall muscles. In the presence of a breast implant, the origin can be related to the fibrous capsule. Primary breast fibromatosis is rare, less than 0.2% of the lesions. It is more common among women at reproductive age, with slow and progressive growth. It tends to be locally aggressive and present recurrence after resection, without metastatic potential. In imaging examinations, they simulate carcinomas. Case report: A 65-year old male patient complaining of palpable nodule in the left breast, with no family history of breast cancer or inherited genetic syndromes. Imaging examinations showed an irregular nodule, with spiculated margins, high density and posterior acoustic shadowing, measuring 1.4 cm (BI-RADS® 5). Percutaneous biopsy of the lesion favored desmoid-type fibromatosis. After sectorectomy, anatomopatho-logical and immunohistochemical examinations confirmed the diagnosis. Discussion: The etiology and physiopathology of these lesions are still not totally known, and it is uncertain whether or not they are part of the abdominal and extra–abdominal fibromatosis spectrum. There are differences in the hormone receptor profile and recurrence rate. Cell proliferation occurs after trauma, hormone stimulation or genetic determination. It can rarely be associated with Gardner’s syndrome or familial multicenter fibromatosis. The treatment consists of surgical excision of the lesion, and radiotherapy can be used in extensive or unresectable tumors. The use of hormone, cytotoxic or anti-inflammatory agents is considered, according to etiology. Tamoxifen can be efficient in negative hormone receptors through the synthetic induction of transforming growth factor beta 1 (TGF b1) through fibroblasts and apoptosis. The highest local recurrence rate occurs in 3 years, when quarterly surveillance is recommended.